Strategi Pengembangan Aneka Dodol Berbasis Bahan Baku Lokal di Kabupaten Lampung Barat - Analianasari Analianasari; Dayang Berliana; Edy Humaidi (Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study was to analyze the strategy of developing various dodol based on local raw materials in Sekincau Village, West Lampung Regency. The method used in this research is SWOT analysis. Respondents were chosen purposively, namely in Desa Sekincau with a sample of 20 respondents and 4 experts who were competent in the knowledge of the development of various dodol based on local raw materials. The results of this study indicate that based on the results of the analysis on the SWOT matrix the recommendations that must be given are the